The new imperialism - Harvey, David , 1935- (Oxford University Press, 2005)
"People around the world are confused and concerned. Is it a sign of strength or of weakness that the US has suddenly shifted from a politics of consensus to one of coercion on the world stage? What was really at stake in the war on Iraq? Was it all about oil and, if not, what else was involved? What role has a sagging economy played in pushing the US into foreign adventurism? What exactly is the relationship between US militarism abroad and domestic politics? These are the questions taken up in this book."-